Pseudovirgaria, a fungicolous hyphomycete genus - U. Braun; P.W. Crous; J.Z. Groenewald (IMA Fungus)
The genus Pseudovirgaria, based on P. hyperparasitica, was recently introduced for a mycoparasite of rust sori of various species of Frommeella, Pucciniastrum and Phragmidium in Korea. In the present study, an older name introduced by Saccardo based on European material, Rhinotrichum griseum, is shown to resemble P. hyperparasitica. Morphological study and ITS barcodes from fresh collections of R. griseum from Austria on uredinia and telia of Phragmidium bulbosum on Rubus spp. reveal that it is distinct from P. hyperparasitica. The status of the genus Rhinotrichum, introduced for a fungus occurring on dry wood, remains unclear. Pseudovirgaria grisea comb. nov. is therefore proposed for the mycoparasite occurring on rust fungi in Europe, and an epitype is designated from the recent collections.